2003
DOI: 10.1046/j.1432-1033.2003.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of S‐nitrosoglutathione by human alcohol dehydrogenase 3 is an irreversible reaction as analysed by electrospray mass spectrometry

Abstract: Human alcohol dehydrogenase 3/glutathione-dependent formaldehyde dehydrogenase was shown to rapidly and irreversibly catalyse the reductive breakdown of S-nitrosoglutathione. The steady-state kinetics of S-nitrosoglutathione reduction was studied for the wild-type and two mutated forms of human alcohol dehydrogenase 3, mutations that have previously been shown to affect the oxidative efficiency for the substrate S-hydroxymethylglutathione. Wild-type enzyme readily reduces S-nitrosoglutathione with a k cat /K m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…It has been suggested that the interplay between the metabolism of GSH and its derivatives, including GSNO and HMGSH, could have a role in regulation of NO signaling via S-nitrosylation of proteins (41). In fact, in mammals, yeast, and E. coli, AdhC is known to catalyze the NADH-dependent reduction of GSNO (30), and it has been proposed that this enzyme protects against nitrosative stress (17,30,42). Interestingly, EstD is not generally considered to play a role in the removal of the products of GSNO reduction (41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the interplay between the metabolism of GSH and its derivatives, including GSNO and HMGSH, could have a role in regulation of NO signaling via S-nitrosylation of proteins (41). In fact, in mammals, yeast, and E. coli, AdhC is known to catalyze the NADH-dependent reduction of GSNO (30), and it has been proposed that this enzyme protects against nitrosative stress (17,30,42). Interestingly, EstD is not generally considered to play a role in the removal of the products of GSNO reduction (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental and computational analyses of these interactions have clarified mechanistic details (60,148,149). High-performance liquid chromatography detection of sulfinamide has also been offered as an indicator of HNO production (34).…”
Section: ð4þmentioning
confidence: 99%
“…As well, the sulfinamide modification imparts a specific mass change to cysteines making sulfinamide analysis, and indirectly HNO analysis, very amenable to investigation by mass spectrometry. The sulfinamide modification has been observed in MS spectra (28), and in a recent mass spectrometric analysis, Shen and English (29) attributed a mass shift of 65 Da on prominent y-ions upon low energy CID to the elimination of the sulfinamide moiety from the molecule in their mass spectrometric comparison of nitroxyl products formed with free and protein-based cysteines. Here we investigate this mass shift and the formation of a previously unstudied neutral loss to determine an efficient method for the identification of the sulfinamide modification and demonstrate its utility on a sample generated by treatment of live platelets immediately post-isolation, that is ex vivo, with HNO.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%